Selectivity of the Traps and Push Net Fishing Gear in the Glass Eels (Anguilla spp.) Capture Fishery in the Cikaso River Waters, Sukabumi, Indonesia - Baihaqi, Faqih; Annida, Shafira Bilqis (International Journal of Contemporary Sciences (IJCS), 2024)
Selectivity is a standard of the level of friendliness of a fishing gear that is reviewed based on the diversity of catches obtained. Nowadays, fishing gear construction and techniques are developed to obtain selective fishing methods. This study compared the selectivity of traps and push nets in glass eel fishing in the Cikaso River, Indonesia. The study was conducted from December 2020 to April 2021. The catch diversity index and relative abundance were used to analyze the selectivity of catch diversity in both fishing gears. Comparative analysis shows that push nets have slightly better selectivity than traps. However, the study's overall results showed a fairly good selectivity of both fishing gears in catching glass eels (Anguilla spp.) as their main catch target.